2012
DOI: 10.1093/cercor/bhs283
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Maturation of the Human Brain From Birth Through Adolescence: Insights From In Vivo Magnetic Resonance Spectroscopy

Abstract: Between birth and late adolescence, the human brain undergoes exponential maturational changes. Using in vivo magnetic resonance spectroscopy, we determined the developmental profile for 6 metabolites in 5 distinct brain regions based on spectra from 309 children from 0 to 18 years of age. The concentrations of N-acetyl-aspartate (an indicator for adult-type neurons and axons), creatine (energy metabolite), and glutamate (excitatory neurotransmitter) increased rapidly between birth and 3 months, a period of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
167
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(184 citation statements)
references
References 72 publications
15
167
1
1
Order By: Relevance
“…As a different methodology for assessing the development of metabolism in the brain, magnetic resonance spectroscopy has been used to determine the developmental profiles of metabolites, such as a marker of axonal and neuronal development, an energy metabolite, and a membrane metabolite, and indicated that the period between birth and 3 mo of age is an immensely active period in metabolite development (54). A comparison of metabolic maturation in preterm-born infants with that of term infants further showed that the metabolic maturation in preterm-born infants, at term equivalence, preceded development in term infants but then, progressed at a slower pace and trajectory (55).…”
Section: Rapid Change Of Hpod From An In-phase To An Antiphase Pattermentioning
confidence: 99%
“…As a different methodology for assessing the development of metabolism in the brain, magnetic resonance spectroscopy has been used to determine the developmental profiles of metabolites, such as a marker of axonal and neuronal development, an energy metabolite, and a membrane metabolite, and indicated that the period between birth and 3 mo of age is an immensely active period in metabolite development (54). A comparison of metabolic maturation in preterm-born infants with that of term infants further showed that the metabolic maturation in preterm-born infants, at term equivalence, preceded development in term infants but then, progressed at a slower pace and trajectory (55).…”
Section: Rapid Change Of Hpod From An In-phase To An Antiphase Pattermentioning
confidence: 99%
“…16,17 MR spectroscopy provides a snapshot of these neurochemical alterations and can also be useful in tracking the progress of a neurologic and/or psychiatric disease in longitudinal studies. Several metabolism alterations have indeed been detected in psychiatric disorders such as schizophrenia, 18 depression, bipolar disorder, 19 and autism spectrum disorder.…”
Section: Why Spectroscopy For Adhd Studies?mentioning
confidence: 99%
“…In humans, levels of myo-inositol decrease over the first 5 years of life, coincident with colonization and stabilization of the intestinal microbiota. 83,84,120 To extend this further, a recent study conducted transcriptional and metabolomics analyses during mouse conventionalization and found positive correlations between measured metabolites and related host metabolic genes. Furthermore, the data suggest that myo-inositol levels decrease upon conventionalization, suggesting a role for the microbiota in regulating these levels.…”
Section: Environmental Enteropathy and Genetic Predispositionmentioning
confidence: 99%
“…Nevertheless, data from human and mouse studies can be combined to start building hypotheses. For example, a recent study measured important brain metabolites from birth to adolescence, 120 some of which are exclusively part of human metabolism (e.g., N-acetylaspartate) and others that are acquired through diet and/or, potentially, the intestinal microbiota (e.g., myo-inositol). In humans, levels of myo-inositol decrease over the first 5 years of life, coincident with colonization and stabilization of the intestinal microbiota.…”
Section: Environmental Enteropathy and Genetic Predispositionmentioning
confidence: 99%